Landscape as heritage international critical perspectives - Pettenati, Giacomo (Routledge Taylor & Francis Group, earthscan from Routledge, 2023)
"This edited book provides a broad collection of current critical reflections on heritage-making processes involving landscapes, positioning itself at the intersection of landscape and heritage studies. Featuring an international range of contributions from researchers, academics, activists and professionals, the book aims to bridge the gap between research and practice and to nourish an interdisciplinary debate spanning the fields of geography, anthropology, landscape and heritage studies, planning, conservation, ecology. It provokes critical enquiry about the challenges between heritage-making processes and global issues, such as sustainability, economic inequalities, social cohesion, and conflict, involving voices and perspectives from different regions of the world. Case studies in Italy, Portugal, Spain, Slovenia, Netherlands, Turkey, UK, Columbia, Brazil, New Zealand, Afghanistan, highlight different approaches, values, and models of governance. This interdisciplinary book will appeal to researchers, academics, practitioners and every landscape citizen interested in heritage studies, cultural landscapes, conservation, geography and planning"